Reliability assessment of electrical equipment of metallurgical plant for separate sections in relation to types of technological production - Yu. N. Kondrashova; A. V. Shalimov; A. M. Markina; A. M. Tretiakov (Омский научный вестник)
At the large industrial enterprise which contains several types of technological lines for maintenance of continuous production process in a power grid complex of the metallurgical enterprise (ME) for realization of a normal mode of the power system operation it is necessary to provide quality of power supply which is defined by reliability and profitability. For evaluation of reliability and condition of electric grid complex it is required to perform analysis of disturbances in operation modes of power supply system of SE with voltage of 10–220 kV during 2007–2020 years. The analysis of the static data of outages showed that the main reasons of power supply failure are short circuits, imposing of several factors and unexplained circumstances, and 70 % of all failures are in cable lines, 25 % — overhead lines and 5 % — failures of power transformers. At present, the connection between electrical equipment and the technological objects being fed depends on their wear and tear. On the example, the main technological processes of ferrous metallurgy production are considered sintering and rolling production, as the most energy-intensive and responsible consumers. It is necessary to identify categories of the most worn-out electrical equipment to develop a set of measures to improve reliability and reduce damages.